Unregistered Marriage (Nikah Sirri) in Tanjung Palas, Indonesia: a Normative-Empirical Analysis Through the Maxim Al-Dhararu Lā Yuzālu bi Al-Dharari - Ratu Haika (CV. Kalimasada Group, 2025)
Purpose - This study examines the persistent phenomenon of nikah sirri (unregistered marriage) in Tanjung Palas District, Bulungan Regency, despite ongoing formal and religious guidance. It aims to explore the socio-legal dynamics underlying the continued practice of nikah sirri and analyze it through the lens of the Islamic legal maxim al-dhararu lā yuzālu bi al-dharari (“harm cannot be eliminated by another harm”). Design/Methodology/Approach - The study employs a normative-empirical design using a qualitative descriptive approach. Primary data were collected through in-depth interviews, observation, and documentation, while secondary data were obtained from books, scholarly articles, the Qur’an, and previous academic works. Data were analyzed through systematic stages of data collection, reduction, presentation, and conclusion drawing. Findings - The findings reveal that nikah sirri is driven by recurring factors, including premarital pregnancy, underage marriage, arranged marriage, intentions to enter polygamous unions, and the absence of divorce certificates from previous marriages. From the perspective of al-dhararu lā yuzālu bi al-dharari, nikah sirri does not serve as a legitimate mechanism for mitigating harm; instead, it creates additional legal and administrative difficulties, particularly in obtaining essential civil documents such as national ID cards, birth certificates, family cards, and other state administrative services.. Originality/Value - This study provides a contemporary evaluation of nikah sirri using the Islamic legal maxim al-dhararu lā yuzālu bi al-dharari, offering a socio-legal perspective that highlights its incompatibility with legal certainty and the protection of family rights within Indonesian society. The research contributes by demonstrating how the practice perpetuates—not eliminates—harm, thus enriching discussions on Islamic legal norms and modern administrative realities. This study contributes to socio-legal discourse by demonstrating that unregistered marriage contradicts Islamic legal principles of harm elimination, thereby supporting state policy on mandatory marriage registration.